Compost maturity and nitrogen availability by co-composting of paddy husk and chicken manure amended with clinoptilolite zeolite - Omar, Latifah; Ahmed, Osumanu Haruna; Kassim, Susilawati; Majid, Nik Muhamad (Sage Publications, 2015)
The availability of paddy husk from rice processing plants remains high owing to increase in the worldwide rice consumption. Increasing demand for chicken products leads to poultry wastes production. Co-composting of the aforementioned wastes could solve the indiscriminate disposal of these wastes. Thus, co-composting of paddy husk and chicken slurry with clinoptilolite zeolite and urea as additive was carried out. Clinoptilolite zeolite was used to enhance ammonium and nitrate retention in the compost. Temperature of the compost was monitored three times daily for 55 days. Cation exchange capacity, organic matter, ash, humic acids, pH, total C, N, C/N ratio; total P, exchangeable Ca, Mg, K, NH4+, NO3−, and heavy metals contents were determined using standard procedures. pH, total N, humic acids, ash, NH4+, NO3−, P, Ca, Mg, and K contents increased but the salinity, heavy metals contents, and microbial population were low after the co-composting process. Zea mays L. (test crop) seed germination rate in distilled water and the compost were not significantly different. Growth of Spinach oleracea (test crop) on a peat-based growing medium and the compost was also not significantly different. These findings were possible because the clinoptilolite zeolite used in co-composting reduced accumulation of heavy metals that may have damage effects on the test crops. Mature compost with good agronomic properties can be produced by co-composting chicken slurry and paddy husk using clinoptilolite zeolite and urea as additives.